Cortical superficial siderosis and acute convexity subarachnoid hemorrhage in cerebral amyloid angiopathy. (23rd November 2017) - Raposo, N.; Calviere, L.; Cazzola, V.; Planton, M.; Patsoura, S.; Wargny, M.; Albucher, J. F.; Sommet, A.; Olivot, J. M.; Chollet, F.; Pariente, J.; Bonneville, F.; et al.
Abstract : Background and purpose: Acute convexity subarachnoid hemorrhage (cSAH) and cortical superficial siderosis (cSS) are neuroimaging markers of cerebral amyloid angiopathy (CAA) that may arise through similar mechanisms. The prevalence of cSS in patients with CAA presenting with acute cSAH versus lobar intracerebral hemorrhage (ICH) was compared and the physiopathology of cSS was explored by examining neuroimaging associations. Methods: Data from 116 consecutive patients with probable CAA (mean age, 77.4 ± 7.3 years) presenting with acute cSAH ( n = 45) or acute lobar ICH ( n = 71) were retrospectively analyzed. Magnetic resonance imaging scans were analyzed for cSS and other imaging markers. The two groups' clinical and imaging data were compared and the associations between cSAH and cSS were explored. Results: Patients with cSAH presented mostly with transient focal neurological episodes. The prevalence of cSS was higher amongst cSAH patients than amongst ICH patients (88.9% vs. 57.7%; P < 0.001). In multivariable logistic regression analysis, focal [odds ratio (OR) 6.73; 95% confidence interval (CI) 1.75–25.81; P = 0.005] and disseminated (OR 11.68; 95% CI 3.55–38.35; P < 0.001) cSS were independently associated with acute cSAH, whereas older age (OR 0.93; 95% CI 0.87–0.99; P = 0.025) and chronic lobar ICH count (OR 0.45; 95% CI 0.25–0.80; P = 0.007) were associated with acute lobar ICH. Conclusions: Amongst patients with CAA, cSS is independently associated with acute cSAH. These findings suggest that cSAH may be involved in the pathogenesis of the cSS observed in CAA. Longitudinal studies are warranted to assess this potential causal relationship.